Katrine & Thorkild Kjærgaard: Ny Herrnhut i Nuuk 1733-2003: Missionsstation, rævefarm, embedsbolig, museum, universitet. - Pedersen, Kenneth (Tidsskriftet Antropologi, 2003)
Anmeldes af Kennet Pedersen